IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH COOPERATIVE SCRIPT ON DESCRIPTIVE TEXT - Nenis Siti Aisyah; Nur Afni Hidayatur Rahma; Rasi Yugafiati (IKIP Siliwangi, 2019)
Abstract This study is revealed based on the observation on the tenth grade of X HT 1 Sangkuriang 2 Vocational High School. The subjects of this study were consisted of 31 students. This study was aimed to improve the students’ vocabulary mastery using Cooperative Script Method. The research design was Classroom Action Research (CAR) which following from Kemmis and Taggart model. It is used to obtain the results of quantitative and qualitative data using 2 cycles described through planning, action, observation, and reflection on each cycle. The result of the study showed that there was a development on the student’s vocabulary mastery. It could be seen from the result of the test. The Minimum Mastery Criteria (KKM) of English lesson was 70. The students mean score in the pre test was 50, in the first post test the mean score was 65, and in the second post test the mean score was 85. In addition there were 2 students (6,4%) who passed KKM on pre test. In the first pretest there were 9 students (29,03%) who passed KKM. In the second pretest there were 29 students (93,55%) who passed KKM. Then, from the result of field notes and interview it showed the positive responses from the students. The students can be more active and improve their ideas. The researcher conclude that Cooperative Script method could improve student’s vocabulary mastery. Keywords: Vocabulary, Cooperative Script, Descriptive Text, CAR